METROLOGICAL PERFORMANCES OF BOMB CALORIMETERS AT REAL CONDITIONS - Yu. V. Maksimuk; Z. A. Antonava; V. S. Krouk; V. V. Fes’ko; V. N. Kursevich; A. F. Syshchanka; I. V. Vasarenko (Приборы и методы измерений)
The high-usage measurement equipment for heat of combustion of organic fuels are bomb isoperibol calorimeters with a water thermostat. The stability of work of calorimeters at real conditions is important for maintenance of reliability of measurement results. The article purpose – the analysis of stability for parameters of calorimeters to environment changes. In this work influence room temperature (Тк) and heat exchange conditions on metrological characteristics of two models of calorimeters is considered with different degree of thermal protection: V-08МА and BIC 100. For calorimeters V-08МА the increase in a effective heat capacity (W) on 0,1 % by growth of Tк on everyone 5 °С is established. To use value W in all interval laboratory temperatures Tк = 14–28 °С it is necessary to correct W on 2,8 J/°C on everyone 1 °С changes of Tк. Updating W is required, if the correction exceeds error in determination W. For calorimeter BIC 100 it is not revealed dependences W from Tк. BIC 100 have constant-temperature cap, high stability a temperature in thermostat and stabilized heat exchange. It is established that an standard deviation of cooling constant for all calorimeters in direct proportional to standard deviation W.